The Role of Islamic Religious Education Teachers in Shaping Student Character in the Digital Era of Class VIII at SMP Islam Plus Sabilunnajah - Barokah, Alvi; Hasyim, Umar Al Faruq A.; Fadilah, Lutfi (International Journal on Advanced Science, Education, and Religion, 2025)
Effective learning is highly dependent on the model used by educators in the teaching and learning process. Quantum Learningis an innovative learning model that aims to create a fun and interactive learning atmosphere to improve student learning outcomes. This study aims to determine student learning outcomes by applying the model.Quantum Learningin mathematics for first-grade students at MI Shodiqussalam Tanjung Jaya. The research method used was a qualitative method with a case study design. Data collection techniques were carried out through observation, interviews, and documentation involving the principal, first-grade teachers, and students. The data obtained were analyzed using data reduction, data presentation, and conclusion drawing techniques. The results of the study showed that the application of the modelQuantum Learninghas a positive impact on student learning outcomes in mathematics lessons on plane geometry based on three main domains, namely cognitive, affective, and psychomotor. In the cognitive aspect, students experienced an increase in understanding of mathematical concepts, especially in plane geometry material. From the affective aspect, students showed higher interest and motivation in learning, as seen from the results of the study which showed that the majority of students felt helped by the applied method. Meanwhile, in the psychomotor domain, students were able to apply mathematical concepts more practically through the use of learning aids. Thus, the modelQuantum Learningproven effective in improving the mathematics learning outcomes of grade I students at MI Shoodiqussalam Tanjung Jaya, so it is recommended to continue to be implemented and developed to improve the quality of learning at the elementary madrasah level.